Network management as a determinant for a successful computer–integrated manufacturing system. (4th August 2014) - Udo, Godwin J.
Network management is a critical success factor for computer–integrated manufacturing (CIM) systems. Telecommunication network management is a new management challenge, which in the past was handled by an outside vendor. The paper gives a description of telecommunications technology management and how it can be used to enhance the integration of technologies, resources, supplier, and customer in a CIM environment. The presentation include a set of management guidelines on how to evaluate, select, and manage telecommunications systems in order to maximise the strategic impact of CIM on organisation.